Simulation Signature-Based Carving Raster Image Using Finite State Automata - Hendra Budi Kusnawan; Windu Gata; Laela Kurniawati (Jurnal Mantik, 2022)
Automata is used as the first stage of describing an idea or example to develop a model, be it software or hardware. Theoretically the concept of automata can be used to simulate the signature-based carving process for identification/recovery of raster type image file PNG and GIF. The research and data collection method used is based on a literature study by explaining the Finite State Automata (FSA) concept in simulating the carving process on an image file. This simulation is a simple example of implementing the automata concept. Even though it is only an abstract machine, automata can be used to simulate various other things that will be solved by computation.